P120 Self taken extragenital sampling – what do women and MSM think? Feedback from a self-swab and clinician swab trial. (30th June 2016) - Wallace, Harriet; Fisher, Jayne; Loftus-Keeling, Michelle; Harrison, Rachel; Daley, Sharon; Wilson, Janet
Abstract : Background/introduction: Extragenital sampling for chlamydia and gonorrhoea is standard practice in MSM and is increasingly important in women. Some UK clinics offer self-swabbing from these sites, but little has been published about its acceptability, particularly in women. We explored this as part of a clinician versus self-swab study. Methods: Women and MSM attending a sexual health clinic were invited to take part in a 'swab yourself' study. Clinician and self-swab samples for chlamydia and gonorrhoea NAATs were taken from the rectum and pharynx. Participants then completed a questionnaire. Results: See table . Response rates were >99% in both women (958/968) and MSM (197/210). MSM were not significantly more likely to feel confident taking their own swabs (83% vs 77%, p = 0.53). Of those who agreed/strongly agreed they 'felt uncomfortable taking their own swabs', sexual naivety of the site was not a common factor (53% of women agreeing stated they had never had anal sex; 70% of men agreeing reported receptive anal sex in the preceding 3 months). Free comments included 'more confidence if had clinician samples taken before', 'concerns if self-swabbing would give accurate results' and concerns about being not able to speak to a healthcare professional with home sampling. 10 women commented specifically on discomfort but only 1/10 disagreed with the statement 'I would feel happy to take my own swabs in a non-clinic environment'. Discussion/conclusion: Extragenital self-swabbing was highly acceptable in both groups, with high levels of confidence and low reports of discomfort. This has positive implications for expanding future use.